Beyond Divergent Thinking: A Longitudinal Study of Creativity Development Trajectories in Adolescents Across Formal and Informal Learning Environments - Zarina Juraeva; Umed Akhmedov; Suhrob Shamsiev (Journal of Loomingulisus ja Innovatsioon, 2026)
Creativity has become a fundamental competency for adolescents navigating increasingly complex educational, technological, and social environments. Conventional research has predominantly conceptualized creativity through divergent thinking, providing limited understanding of how creativity develops over time across multiple learning contexts. This study aimed to examine longitudinal creativity development trajectories among adolescents by investigating the interactions among formal schooling, informal learning experiences, creative self-efficacy, intrinsic motivation, creative identity, and collaborative engagement. A mixed-methods longitudinal sequential explanatory research design was employed involving 720 secondary school students observed across four measurement waves over three years. Quantitative data were collected using standardized creativity, motivation, self-regulated learning, and creative identity instruments, complemented by academic records, extracurricular participation logs, and digital portfolio analytics. Qualitative evidence was obtained through semi-structured interviews, focus group discussions, classroom observations, family interviews, reflective journals, and portfolio analysis. Findings revealed significant longitudinal improvements in creative thinking, creative self-efficacy, intrinsic motivation, self-regulated learning, collaborative competence, creative identity, and academic achievement. Adolescents who consistently participated in both formal and informal learning environments demonstrated stronger creativity trajectories than peers relying primarily on classroom instruction. Qualitative findings further indicated that sustained creativity development emerged through continuous interaction among supportive educational relationships, authentic learning experiences, learner autonomy, and reflective practice. Results suggest that creativity should be understood as a multidimensional developmental process extending beyond divergent thinking, providing an integrated framework for designing educational ecosystems that cultivate lifelong creativity among adolescents.